A retrospective cohort study evaluating the predictive value of urinary L-FABP combined with the SOFA score for assessing COVID-19 severity - Kanako Terakawa; Daisuke Katagiri; Yusuke Asai; Masahiro Ishikane; Norio Ohmagari; Minami Suzuki; Masayuki Hojo; Hideki Takano; Katsushi Tokunaga; Takeshi Sugaya; Eisei Noiri (PLoS ONE, 2025)
Although the symptoms of Coronavirus Disease 2019 (COVID-19) omicron strains are generally mild, some individuals with initially mild symptoms later required supplemental oxygen or hospitalization, while others died, highlighting the importance of rapid diagnosis and early treatment for such patients. Therefore, this study evaluated the benefit of a combined approach to identify individuals at risk of severe illness due to COVID-19 using urinary L-type fatty acid-binding protein (L-FABP) levels and the Sequential Organ Failure Assessment (SOFA) scores calculated from blood tests for pre-admission screening of patients with COVID-19. L-FABP, a non-invasive urine biomarker, and the SOFA score, an established method for assessing organ failure severity, were evaluated in conjunction with patient data collected from 842 individuals admitted to a hospital in Tokyo, Japan. The combined approach demonstrated a higher accuracy in identifying patients at risk of severe illness compared to the L-FABP levels or SOFA scores alone. Thus, the results suggest that a two-tiered screening process, utilizing measurement of L-FABP levels as an initial rapid test, followed by SOFA score assessment for high-risk patients, results in efficient pre-admission screening and improved patient management. In conclusion, this study underscores the potential of combining L-FABP levels and SOFA scores for optimizing patient care during the ongoing COVID-19 pandemic, emphasizing the need for further validation and refinement of the predictive models.